2020
DOI: 10.1177/0898264320935238
|View full text |Cite
|
Sign up to set email alerts
|

Family Ties and Aging in a Multiethnic Cohort

Abstract: Objective: Lack of social support is linked to lower cognitive function and cognitive decline. We investigated the effects of a specific type of social relationship, family ties, on cognitive trajectories in non-Hispanic whites, non-Hispanic blacks, and Hispanics. Methods: Using multiple-group latent growth curve models, we analyzed associations between the number of children/grandchildren/siblings/other relatives contacted within the past month at baseline and cognitive trajectories in 1420 older adults who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 54 publications
1
8
2
Order By: Relevance
“…The number of family members other than children and spouse showed negative associations with executive function, visuoconstruction, and processing speed. This finding contrasts somewhat with some previous research showing positive relationships between the number of noncentral family members and cognitive outcomes (Ying et al, 2020). However, it should be noted that siblings were included in the “other family member” category in the present study but were excluded in the “other family member” category in the study by Ying et al (2020), which posited that contact with a greater number of peripheral family members may be mentally stimulating in a way similar to friendships.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The number of family members other than children and spouse showed negative associations with executive function, visuoconstruction, and processing speed. This finding contrasts somewhat with some previous research showing positive relationships between the number of noncentral family members and cognitive outcomes (Ying et al, 2020). However, it should be noted that siblings were included in the “other family member” category in the present study but were excluded in the “other family member” category in the study by Ying et al (2020), which posited that contact with a greater number of peripheral family members may be mentally stimulating in a way similar to friendships.…”
Section: Discussioncontrasting
confidence: 99%
“…Greater contact frequency with family (Béland et al, 2005) and children (Zahodne et al, 2019) may also have potentially beneficial effects. There is also support for positive relationships between the number of noncentral family members an individual contacts and cognitive outcomes (Ying et al, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In that regard, our finding demonstrated that the higher the participant’s satisfaction with their family partnership, empathy, support, affection and interaction, the better their cognitive performance. Contradicting other studies with the U.S. and Chinese population ( Sims et al, 2014 ; Ge et al, 2017 ; Li et al, 2019 ), our findings that high emotional support was associated with better cognitive performance is consistent with much evidence reporting protective effects of functional support on cognition ( Seeman et al, 2001 ; Windsor et al, 2014 ; Kelly et al, 2017 ; Ying et al, 2020 ; Costa-Cordella et al, 2021 ). Social interactions are cognitively and emotionally processed by the brain, socially supportive interactions may contribute to better cognitive aging through direct positive stimulatory effects on the brain ( Seeman et al, 2001 ).…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, qualitative and biological elements that underpin the relationship between social network and cognition is quite limited. For example, family ties represent an essential network source among older adults ( Ying et al, 2020 ). A few studies investigated the impact of family support on cognitive performance with varied results ( Windsor et al, 2014 ; Ge et al, 2017 ; Ying et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation